TREE CARBON STOCK ESTIMATION AND MODELING OF PALSABANGON WATERSHED USING THE INVEST MODEL IN QUEZON PROVINCE, PHILIPPINES - Raffy D. Gordula; Nelson M. Pampolina; Cristino L. Tiburan Jr.; Inocencio E. Buot Jr. (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTS- First carbon mapping of Palsabangon watershed using InVEST model- Combines remote sensing and field data across four key vegetation types- Reveals mangroves store highest carbon per hectare among land covers- Secondary forests hold largest total carbon due to broader area coverage- Informs creation of carbon conservation zones in vulnerable watershed areasABSTRACTThe Palsabangon Watershed is primarily composed of young secondary forests, shrublands, agroforestry, and remnant mangrove stands that are increasingly threatened by land-use conversion, resource extraction, and natural disturbances. The watershed remains undeclared and unprotected by law in the southern Sierra Madre Mountain Range of Quezon Province, Philippines. Despite these pressures, the watershed continues to play an important role in carbon sequestration and climate regulation. To assess carbon stock, four vegetation types; secondary forest, shrubland, agroforestry, and mangrove were evaluated through quadrat sampling using thirteen 5 m × 40 m rectangular plots. Tree carbon was estimated using allometric equations, and land use/land cover maps were generated from Sentinel-2 satellite imagery. The dominant vegetation cover was secondary forest, followed by shrubland, agroforestry, and mangrove forest. Carbon stock estimation was performed using the Carbon Storage and Sequestration model within the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) software. The estimates of tree carbon stock (C) in Palsabangon Watershed revealed that mangrove forests had the highest density (85.1 MgC/ha), followed by secondary forests (67.8 MgC/ha), agroforestry (50.4 MgC/ha), and shrublands (43.3 MgC/ha). Tree carbon stock in mangroves and secondary forests was attributed to the younger age and declining tree density of these ecosystems, caused by anthropogenic and natural factors. The total tree carbon stock of the watershed was estimated at 295,674 tonnes C, with secondary forests contributing the most (140,666.7 tonnes C). Despite the young age of the forest stands, the watershed demonstrates significant potential for carbon accumulation. To ensure long-term sustainability, we recommend the establishment of forest carbon conservation zones to protect and enhance carbon sequestration capacity of the watershed.